Features of the Calculated Determination of the Thermal State of the Turbo Generator Brush-Contact Device - Anton Ye. Kovryha (Journal of Mechanical Engineering)
The features of the calculation of the thermal state of the turbo generator brush-contact device are discussed in this paper. The author provides an algorithm for analytical calculation of the device, determines the expected temperatures of the elements provided that additional filters are installed in the ventilation duct. Using the finite element method, a three-dimensional calculation of the thermal state of the brush-contact device elements was performed. The obtained results confirm the possibility of improving the design of the brush-contact device by installing filtering elements in order to increase the reliability of the operation of this unit.